Increasing Transmission Reliability for Telemetry Systems Using Telegram Splitting - Kilian, Gerd; Breiling, Marco; Petkov, Hristo; Lieske, Hendrik; Beer, Frederik; Robert, Jörg; Heuberger, Albert (IEEE Transactions on Communications, 2015)
This paper analyzes the reliability and throughput of the telegram-splitting concept in the presence of inter-system and intra-system interference. Using telegram splitting, the data of one telegram is split into multiple sub-packets, which are then transmitted with temporal spacing. As a result, collisions with other telegrams destroy only some sub-packets that can be recovered using forward error correction. Consequently, the reliability of the data transmission in case of inter-and intra-system interference-a significant problem in license-exempt bands-is highly improved. In this paper, probabilities for the resulting telegram error rate of random media access systems using telegram splitting are derived. Furthermore, the achievable throughput is analyzed. The theoretical considerations in addition to simulation results prove the significant gain of the telegram-splitting concept for telemetry systems.
Keywords: Telemetry; multiuser channels; interference